United States Infrastructure Investments by State Governments : Grading the Decision Process - Petersen, John E.; Vu, Ha T.T. (World Bank, Washington, DC, 2015)
As with any large scale governmental activity, there are always questions about how well a function is performed in accomplishing its manifold objectives: are decisions well informed, coordinated, and cost effective? In the case of public investments, these issues are all the more important because of the large sums and long horizons involved, which make them particularly significant in terms of their consequences for an economy. Unless the vital services provided by infrastructure are effectively performed when and where needed, economies will flag and private needs will go unmet. This report examines the general contours of infrastructure spending and financing in the United States. With a couple of notable exceptions, most of that spending is done at the state and local government level. An assessment of infrastructure decision making examines the results of two recent surveys of state governmental management practices performed by the pew center for the states. These surveys contain a subset of factors that provide indices of the quality of infrastructure planning and management in the individual states. These results allow comparisons among the states and between the two periods, allowing one to take a cursory look at the correlation between the grades and other characteristics of the states.